The Dialectic of Faith and Reason in Cornelio Fabro's Reading of Kierkegaard's Theology - Furnal, Joshua (Theological studies, 2017)
This essay explores the impact of Søren Kierkegaard upon the important Italian Thomist, Cornelio Fabro. Fabro rejected the caricature of Kierkegaard as an irrationalist and placed him firmly in the Christian tradition. By highlighting the influence of Kierkegaard upon a Thomist like Fabro, the relevance of Fabro's own thought is opened up for more contemporary debates in theology regarding the enduring legacies of German idealism, existentialism, and atheism.